MENELISIK PERKEMBANGAN HOLISTIK PESERTA DIDIK TERHADAP PENGUATAN PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Naila Tsaqinah; Navilla Ratu Bilqis; Rahmawati Eka Saputri (STKIP Subang, 2025)
This research intends to investigate the connection between students' overall development and the promotion of character education in elementary schools. Character education is critical in developing a generation that succeeds not just academically but also morally, with honesty, compassion, and social responsibility. Using a descriptive qualitative methodology through literature review, this study examines how the application of a holistic approach can aid in the overall growth of student character. The results suggest that comprehensive education, which includes cognitive, emotional, social, physical, and spiritual elements, has a beneficial impact on students' self-awareness, attitudes, and behavior. Furthermore, the effectiveness of these programs is strongly influenced by cooperation between schools, parents, and communities. These results highlight the value of using comprehensive education as a primary approach for sustainably increasing character education in elementary schools.